2013
DOI: 10.1007/s00894-013-2023-5
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the scavenging activity of ellagic acid and its methyl derivatives towards hydroxyl, methoxy, and nitrogen dioxide radicals

Abstract: The reaction mechanisms involved in the scavenging of hydroxyl (OH(·)), methoxy (OCH₃(·)), and nitrogen dioxide (NO2 (·)) radicals by ellagic acid and its monomethyl and dimethyl derivatives were investigated using the transition state theory and density functional theory. The calculated Gibbs barrier energies associated with the abstraction of hydrogen from the hydroxyl groups of ellagic acid and its monomethyl and dimethyl derivatives by an OH· radical in aqueous media were all found to be negative. When NO₂… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…The scavenging efficacy of an antioxidant can be determined with the scavenging rate constant, which is the rate of the compoundʼs reaction with free radicals in a given system. Tiwari and Mishra [56] ). These authors thus suggested that ellagic acid should, in general, be a more efficient scavenger of ROS than of reactive nitrogen species.…”
Section: Ellagic Acid As An Antioxidant Agentmentioning
confidence: 99%
“…The scavenging efficacy of an antioxidant can be determined with the scavenging rate constant, which is the rate of the compoundʼs reaction with free radicals in a given system. Tiwari and Mishra [56] ). These authors thus suggested that ellagic acid should, in general, be a more efficient scavenger of ROS than of reactive nitrogen species.…”
Section: Ellagic Acid As An Antioxidant Agentmentioning
confidence: 99%
“…EA antioxidant activity can be considered comparable to that of well-known essential vitamins, like ascorbic acid and α-tocopherol [35], and more efficient against reactive oxygen species (ROS) than reactive nitrogen species [36]. Furthermore, phenolic compounds like EA are able to hinder the prooxidative action of metals (copper, iron, nickel, cadmium) by chelation [37,38] and directly interact with DNA causing a significant decrease of 8-oxo-2-deoxyguanosine levels, a typical marker of oxidative DNA damage [39][40][41].…”
Section: Biological Properties and Clinical Applications Of Ellagic Acidmentioning
confidence: 99%
“…Based on the calculated thermodynamic parameters, they have suggested that the hydrogen atom transfer (HAT) is the most favorable mechanism in nonpolar media, whereas sequential proton loss electron transfer (SPLET) is preferred in polar media, which is in agreement with results reported by Mazzone et al [ 21 ]. Utilizing the transition state theory, Tiwari and Mishra have determined the rate constants for the reactions of EA (as well as its monomethyl and dimethyl derivatives) with hydroxyl (HO • ), methoxy (CH 3 O • ) and nitrogen dioxide (NO 2 • ) radicals [ 22 ]. However, the calculated rate constants of HO • and CH 3 O • radicals have been overestimated by several orders of magnitude in comparison with the experimentally obtained values [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%